Technik der Proktokolektomie mit ileoanalem Pouch: Standards und Kontroverses = The technique of restorative proctocolectomy with ileal J-pouch : standards and controversies - Hardt, Julia; Kienle, Peter (Der Chirurg, 2017)
Background: Restorative proctocolectomy (RPC) is the standard of care in the case of medically refractory disease and in neoplasia in ulcerative colitis (UC). Objectives: This review aims at providing an overview of the current evidence on standards, innovations, and controversies with regard to the surgical technique of RPC. Results: RPC is the standard of care in the surgical management of UC refractory to medical treatment and in neoplasia. Due to its simplicity and good functional outcomes, the J‑pouch is the most used pouch design. RPC is usually performed as a two-stage procedure. In the presence of risk factors, a three-stage procedure should be performed. The technically more demanding mucosectomy and hand sewn anastomosis does not seem to result in a better oncologic outcome than stapled anastomosis. Functional results appear marginally better after stapled anastomosis, but the rectal cuff should not exceed 2 cm in this reconstruction. The laparoscopic approach is at least as good as the open approach. For the new, innovative surgical approaches such as robotics and transanal surgery, only feasibility but no advantages have yet been demonstrated. Conclusion: The evidence in regard to controversial points remains limited.